Evaluation of cationic polyamidoamine dendrimers’ dermal toxicity in the rat skin model - Winnicka K; Wroblewska M; Sosnowska K; Car H; Kasacka I (Dove Medical Press, 2015)
Katarzyna Winnicka,1 Magdalena Wroblewska,1 Katarzyna Sosnowska,1 Halina Car,2 Irena Kasacka3 1Department of Pharmaceutical Technology, Faculty of Pharmacy, Medical University of Bialystok, Bialystok, Poland; 2Department of Experimental Pharmacology, Faculty of Health Sciences, Medical University of Bialystok, Bialystok, Poland; 3Department of Histology and Cytophysiology, Faculty of Pharmacy, Medical University of Bialystok, Bialystok, Poland Abstract: Polyamidoamine (PAMAM) dendrimers are multi-branched, three-dimensional polymers with unique architecture, which makes these molecules attractive for medical and pharmaceutical applications. Using PAMAM as drug carriers for topical delivery might be beneficial as they only produce a transient effect without skin irritation. To evaluate the dermal toxicity of cationic PAMAM dendrimers generation 2 and generation 3, skin irritation studies were performed in vivo in the rat skin model. After 10 days topical application of various concentrations of PAMAM-NH2 (0.3 mg/mL, 3 mg/mL, 6 mg/mL, 30 mg/mL, 300 mg/mL), skin irritation was evaluated by visual, histopathological, and immunohistochemical examination. Microscopic assessment after hematoxylin-eosin staining revealed significant morphological changes of epidermal cells after application of PAMAM-NH2 at a concentration of ≥6 mg/mL. Morphological alterations of epidermal cells included cytoplasmic vacuolization of keratinocytes in the basal and spinous layers. Cytomorphological changes in keratinocytes, overall picture of the epidermis, and histopathological changes in the dermis were dose dependent. Detected alterations concerned hyperplasia of connective tissue fibers and leukocyte infiltration. Visible granulocyte infiltration in the upper dermis and sockets formed by necrotic, cornified cells in the hyperplastic foci of epithelium were also noted. Immunohistochemical analyses revealed that increased nuclear immunoreactivity to PCNA correlated with the concentration of PAMAM-NH2, but no significant differences in the cell proliferation activity in skin treated with PAMAM-NH2 generation 2 or generation 3 were observed. Significantly higher expression of PCNA extended throughout the skin layers might suggest abnormal cell proliferation, which, as a consequence, might even lead to neoplastic changes. Keywords: cationic PAMAM dendrimers polymers, topical delivery, nanomaterials, in vivo toxicity, skin irritation test